Morphological and Volumetric Analysis of Left Atrial Appendage and Left Atrium: Cardiac Computed Tomography-Based Reproducibility Assessment - Taina, Mikko (Public Library of Science, 2014)
OBJECTIVES: Left atrial appendage (LAA) dilatation and morphology may influence an individual's risk for intracardiac thrombi and ischemic stroke. LAA size and morphology can be evaluated using cardiac computed tomography (cCT). The present study evaluated the reproducibility of LAA volume and morphology assessments. METHODS: A total of 149 patients (47 females; mean age 60.9±10.6 years) with suspected cardioembolic stroke/transient ischemic attack underwent cCT. Image quality was rated based on four categories. Ten patients were selected from each image quality category (N = 40) for volumetric reproducibility analysis by two individual readers. LAA and left atrium (LA) volume were measured in both two-chamber (2CV) and transversal view (TV) orientation. Intertechnique reproducibility was assessed between 2CV and TV (200 measurement pairs). LAA morphology (A = Cactus, B = ChickenWing, C = WindSock, D = CauliFlower), LAA opening height, number of LAA lobes, trabeculation, and orientation of the LAA tip was analysed in all study subjects by three individual readers (447 interobserver measurement pairs). The reproducibility of volume measurements was assessed by intra-class correlation (ICC) and the reproducibility of LAA morphology assessments by Cohen's kappa. RESULTS: The intra-observer and interobserver reproducibility of LAA and LA volume measurements was excellent (ICCs>0.9). The LAA (ICC = 0.954) and LA (ICC = 0.945) volume measurements were comparable between 2CV and TV. Morphological classification (ĸ = 0.24) and assessments of LAA opening height (ĸ = 0.1), number of LAA lobes (ĸ = 0.16), trabeculation (ĸ = 0.15), and orientation of the LAA tip (ĸ = 0.37) was only slightly to fairly reproducible. CONCLUSIONS: LA and LAA volume measurements on cCT provide excellent reproducibility, whereas visual assessment of LAA morphological features is challenging and results in unsatisfactory agreement between readers.